1992
DOI: 10.1042/cs0830503
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous release of interleukin-1 and interleukin-6 by peripheral blood mononuclear cells after oophorectomy

Abstract: 1. We studied the changes in interleukin-1 and interleukin-6 secretion by peripheral blood mononuclear cells from 12 premenopausal women after oophorectomy and seven premenopausal women who had undergone simple hysterectomy. 2. The results showed that 1 month after surgery interleukin-1 secretion increased by 414 +/- 171% (mean +/- SEM) and interleukin-6 secretion increased by 1354 +/- 481% in oophorectomized women, whereas only non-significant fluctuations in the secretion of both cytokines (-9% +/- 29% for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…In this study we found that MSups from OVX, SHAM, and OVX+E mice stimulated PG production in calvarial cultures (19)(20)(21)(22)(23)(24)(25)(26)(27). IL-1, a proinflammatory cytokine, is principally produced by activated macrophages (43) but can also be synthesized by bone cells and adjacent hematopoietic cells (43,44).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this study we found that MSups from OVX, SHAM, and OVX+E mice stimulated PG production in calvarial cultures (19)(20)(21)(22)(23)(24)(25)(26)(27). IL-1, a proinflammatory cytokine, is principally produced by activated macrophages (43) but can also be synthesized by bone cells and adjacent hematopoietic cells (43,44).…”
Section: Discussionmentioning
confidence: 91%
“…IL-i has been shown to increase PGHS protein and mRNA and to activate PLA2 in other cell types (47)(48)(49)(50)(51)(52). A role for IL-1 in postmenopausal bone loss is supported by studies showing that both natural and surgical menopause are associated with increased production of IL-1 bioactivity in cultured monocytes and that this effect is reversed by estrogen replacement (19)(20)(21)(22). Recently, in vivo administration of IL-ira was found to inhibit bone loss in ovariectomized rats (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these factors may be under the controlling influence of steroid hormones (12)(13)(14)(15)(16)(17) (18), thymic lymphocytes (18,19), and lymphoid cells present in human endometrium (20). Studies indicate that either in vitro or in vivo exposure to this steroid or pituitary peptides affects cytokine secretion and gene expression by leukocytes and endometrial cells (12)(13)(14)(15)(16)(17). For example, peripheral blood leukocytes spontaneously release significantly increased levels of IL-1 and IL-6 after oophorectomy as compared to women who had undergone hysterectomy without removal of ovaries (16).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that either in vitro or in vivo exposure to this steroid or pituitary peptides affects cytokine secretion and gene expression by leukocytes and endometrial cells (12)(13)(14)(15)(16)(17). For example, peripheral blood leukocytes spontaneously release significantly increased levels of IL-1 and IL-6 after oophorectomy as compared to women who had undergone hysterectomy without removal of ovaries (16). Moreover, ovarian ablation was accompanied by alterations in serum levels of plasma proteins associated with bone loss.…”
Section: Introductionmentioning
confidence: 99%